Hypericum perforatum hydroxyalkylpyrone synthase involved in sporopollenin biosynthesis – phylogeny, site‐directed mutagenesis, and expression in nonanther tissues. (28th July 2014) - Jepson, Christina; Karppinen, Katja; Daku, Rhys M.; Sterenberg, Brian T.; Suh, Dae‐Yeon
<x xml:space="preserve">Abstract</x> Anther‐specific chalcone synthase‐like enzyme (ASCL), an ancient plant type III polyketide synthase, is involved in the biosynthesis of sporopollenin, the stable biopolymer found in the exine layer of the wall of a spore or pollen grain. The gene encoding polyketide synthase 1 from Hypericum perforatum (HpPKS1) was previously shown to be expressed mainly in young flower buds, but also in leaves and other tissues at lower levels. Angiosperm ASCLs, identified by sequence and phylogenetic analyses, are divided into two sister clades, the Ala‐clade and the Val‐clade, and HpPKS1 belongs to the Ala‐clade. Recombinant HpPKS1 produced triketide and, to a lesser extent, tetraketide alkylpyrones from medium‐chain (C6) to very long‐chain (C24) fatty acyl‐CoA substrates. Like other ASCLs, HpPKS1 also preferred hydroxyl fatty acyl‐CoA esters over the analogous unsubstituted fatty acyl‐CoA esters. To study the structural basis of the substrate preference, mutants of Ala200 and Ala215 at the putative active site and Arg202 and Asp211 at the modeled acyl‐binding tunnel were constructed. The A200T/A215Q mutant accepted decanoyl‐CoA, a poor substrate for the wild‐type enzyme, possibly because of active site constriction by bulkier substitutions. The substrate preference of the A215V and A200T/A215Q mutants shifted toward nonhydroxylated, medium‐chain to long‐chain fatty acyl‐CoA substrates. The R202L/D211V double mutant was selective for acyl‐CoA with chain lengths of C16–C18, and showed a diminished preference for the hydroxylated acyl‐CoA substrates. Transient upregulation by abscisic acid and downregulation by jasmonic acid and wounding suggested that HpPKS1, and possibly other Ala‐clade ASCLs, may be involved in the biosynthesis of minor cell wall components in nonanther tissues.